2010
DOI: 10.1375/bech.27.2.84
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Impaired Event-Based Prospective Memory in Clinical Obsessive–Compulsive Checking

Abstract: Based on findings from subclinical OCD checking samples (Cuttler & Graf, 2007; 2008), Cuttler and Graf (2009) suggested that checking may develop to compensate for prospective memory failures. The present study provides the first evidence of prospective memory problems in a clinical sample of OCD checkers (n = 26) compared to a group of healthy controls (n = 26). Consistent with earlier work with subclinical samples, the OCD checkers performed more poorly on an event-based, but not a time-based, prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
2
16
1
Order By: Relevance
“…Regarding the subjective report of PM in everyday life, OCD patients did not make more complaints in PM failures compared to healthy controls Harris et al, 2010). This is in contrast to the elevated PM complaints in subclinical populations (Cuttler and Graf, 2007;.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…Regarding the subjective report of PM in everyday life, OCD patients did not make more complaints in PM failures compared to healthy controls Harris et al, 2010). This is in contrast to the elevated PM complaints in subclinical populations (Cuttler and Graf, 2007;.…”
Section: Introductionmentioning
confidence: 59%
“…This finding is consistent with our hypothesis and previous studies, as time-based PM is usually the most severely impaired among the three types of PM (Henry et al, 2004;Wang et al, 2009). In the only study that investigated time-based PM in OCD patients with checking as the main symptom, Harris et al (2010) found no impairment in time-based PM.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations